Ionotropic glutamate receptors and their implications in cancer and cancer therapeutics - Shree Goyal; Pallab Chakraborty; Balasubramaniam Shankar (Biomedical and Biotechnology Research Journal, 2021)
Glutamine, an excitatory neurotransmitter, is necessary for physiological as well as pathological processes. Other than neuronal disorders and/or cancers, glutamate receptors have also been associated with an array of other malignancies. The metabotropic glutamate receptor (mGluR 1–8 [like Groups I, II, and III]) and ionotropic glutamate receptor (iGluR) have been targeted to treat cancers like carcinoma of the lung, breast, prostate, and oral cancer. iGluRs present on N-methyl-D-aspartate (NMDA) and non-NMDA receptors are multisubunit complexes. Since these subunits of NMDA receptors influence the mTOR signaling pathway significantly, their antagonists such as memantine, ifenprodil, or diclozipine are often used in cancer chemotherapy. Non-NMDA receptors such as α-amino 3-hydroxyl-5-methyl-4-isoxazole-propionate (AMPA) and kainate undergo glutamine to arginine site-specific RNA editing inflicting changes in cancer cell permeability. Thus, the employment of antagonists specific to these receptors would provide an effective anticancer therapeutic approach. Since AMPA receptors and kainate receptors have a crucial role in neural development and other cellular processes, their contribution in tumorigenesis has been mainly recognized in brain tumors although their role in further cancers cannot be ruled out. Delta or orphan receptors are primarily classified based on sequence homology. The effect and activity of antagonists for metabotropic and iGluRs have been pointed out due to their remedial contribution in various tumors. This review also highlights the relation of a range of subunits to cancer and anticancer agents as curatives for future applications and investigations.